Efficient trade matrix and gold reserve requirement for commodity trade among OIC countries - Yusuf, Muhammad-Bashir; Meera, Ahamed Kameel Mydin; Mat Ghani, Gairuzazmi; Abdul Manap, Turkhan Ali; Larbani, Moussa (IDOSI Publications, 2012)
Abstract: The triple crises of 2008 with its enormous impact on the world trade have made many countries to start to look inward on how to prevent or curtail the future re-occurrence and impact. The Organization of Islamic Cooperation Countries should not be left out of the effort to beat future crises of this nature. To do this, they need to look inward and strengthen the intra trade among one another. To achieve this, they need a common platform in terms of trade coordination and a generally accepted international reserve currency that will be stable and will not be a potential source of crises in itself. All these require a proper strategic planning and evaluation of what is and what is supposed to be. This study is one of the earliest works in that direction. This study used a non linear mathematical programming to analyze the efficient trade matrix among OIC countries and the gold reserve requirements for every single country that participate in that trade. It was discovered that trade among these countries could be maximized based on the output of the analysis. The quantities of gold required by each of the country to participate in the multi-bilateral and multilateral trade were also found out. It was also discovered that the quantity of gold needed for such trade was least in multilateral trade arrangement. This study has a lot of implications in strengthen the cooperation among OIC countries and maximizing the trade relationship among them.